Dytocia in Mare due to Lateral Deviation of Head in a Congenitally Deformed Foal - DADARWAL, DINESH; HONPARKHE, M; DHALIWAL, G S (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia in a mare related with the congenitally deformed foal is presented.
Keywords: Congenital deformity; Dystocia; Mare; Scoliosis